Bibliometric Analysis of Employee Procrastination Behavior: A Lack of Contribution to Organizational Productivity (West Science Business and Management, 2025)
Procrastination behavior among employees is a growing concern in organizational settings, negatively impacting productivity and overall work efficiency. This study conducts a bibliometric analysis of scientific literature on employee procrastination and its effect on organizational productivity, focusing on the trends, research gaps, and collaboration patterns from 2015 to 2025. Using data from academic databases such as Scopus, Web of Science, and Google Scholar, the study identifies key publications, analyzes the evolution of research topics, and assesses the contributions of various authors in this field. The results reveal a significant increase in studies related to procrastination in the workplace, with a focus on time management, leadership influence, and the role of organizational culture in mitigating procrastination. The findings suggest that understanding the underlying causes of procrastination and implementing strategies to address it can lead to improved organizational performance. This research offers valuable insights for human resource management and sets the foundation for future studies in addressing procrastination in the workplace.